THE YOUTH AND THEIR ACHIEVEMENTS. YOUTH POLICY IN UZBEKISTAN - Teshaboyeva , Nafisa; Jonizoqova , Farangiz (Effective scientific journals, 2025)
The Youth and Their Achievements: Youth Policy in Uzbekista This article explores the dynamic role of Uzbekistan's youth in shaping the nation's future, highlighting their remarkable achievements across education, sports, culture, and innovation. As the "golden generation," Uzbek youth have propelled the country to rapid progress, evidenced by its ascent in the global Youth Development Index and top rankings in UN youth initiatives. Key accomplishments include over 900 gold medals in international sports competitions, breakthroughs in IT and fintech startups attracting billions in investments, and cultural contributions that enrich national identity.Central to these successes is Uzbekistan's comprehensive youth policy, outlined in the Concept for Development until 2025 and complemented by a detailed Roadmap. Under President Shavkat Mirziyoyev's leadership, initiatives emphasize education, entrepreneurship, employment, and digital safety, fostering patriotism and global engagement. The 2025 National Youth Statement encapsulates youth-led policy suggestions, promoting inclusive opportunities to combat poverty and drive economic growth. Challenges such as digital threats and employment gaps are addressed through targeted programs, ensuring equitable development.The article argues that empowering youth not only celebrates their achievements but also positions Uzbekistan as a model for sustainable youth policies in Central Asia. By integrating global standards with local values, the nation is building a resilient, innovative society ready for the 21st century.